Carbazoles and Hydrazone‐Bridged Thiazole‐Pyrrole Derivatives as New Inhibitors of α‐Glucosidase. Issue 27 (20th July 2018) - Ghani, Usman; Albarrag, Ahmed; Yurttaş, Leyla; Demirci, Fatih; Kaplancikli, Zafer Asim
Abstract: Carbazoles and hydrazone‐bridged thiazole‐pyrrole derivatives are known to exhibit a wide range of biological activities including antimicrobial activity. This work is a further extension of their biological activities that identifies a total of 13 of these derivatives as new α‐glucosidase inhibitors. The carbazole derivatives exhibited noncompetitive inhibition of the enzyme with the inhibitor possessing the 2‐benzoimidazole substitution being the most potent in the series. Compounds possessing the 2‐benzothiazole, 2‐benzoxazole and quinoline groups were also found to be promising for enzyme inhibition. The hydrazone‐bridged thiazole‐pyrrole derivatives showed competitive enzyme inhibition with a number of groups responsible for potent enzyme inhibition including 4‐nitrophenyl, 4‐bromophenyl, and 4‐methoxyphenyl groups. Moreover, the hydrazone derivatives with unsubstituted pyrrole ring were found to be more favorable to α‐glucosidase inhibition than the ones possessing the methyl‐substituted ring. The current work may provide new structural and functional diversity to drug discovery of promising α‐glucosidase inhibitors as anti‐diabetic drugs. Abstract : Carbazoles and hydrazone‐bridged pyrrole derivatives are identified as new noncompetitve and competitive inhibitors of α‐glucosidase respectively. Carbazoles with 2‐benzoimidazole group and hydrazones with unsubstituted pyrrole ring exhibited potent inhibition of the enzyme. This work adds new structural diversity to drug discovery of α‐glucosidase inhibitors for treatment of diabetes mellitus.